Identifying the Threshold Level of Flooding for Rice Production in Bangladesh: An Empirical Analysis - Mohammad Chhiddikur Rahman; Mohammad Ariful Islam; Md Shajedur Rahaman; Md Abdur Rouf Sarkar; Rokib Ahmed; Md Shahjahan Kabir (Journal of the Bangladesh Agricultural University, 2021)
Flood is responsible for the agricultural production scheme and livelihood well-being in Bangladesh. It is the most frequent catastrophe that affects crop production in terms of area coverage and yield. However, a normal flood is beneficial for the ecology and environment. As rice is the most important crop for sustaining the food security of the country, this study identified the threshold level of flooding for rice area coverage and production. The study used the time series data of annual rice area coverage, production, and flooding area in a well-established threshold regression model. The empirical results expose that flooding 22 percent of the geographical area is the threshold value for rice area coverage and production in Bangladesh. Up to the threshold level (22 percent), a one square kilometer increase in flooding would increase the rice area coverage by 31 hectares, as flooding would bring more land under cultivation. Beyond the threshold limit, a one square kilometer increase in flooding would reduce the rice area coverage by 2 hectares. On the other hand, the production of rice would increase by 492 tons with a one square kilometer increase in flooding up to the threshold limit. However, the rice production would reduce by 70 tons if a one square kilometer increase flooding above the threshold limit. On top of that, both the rice area coverage and production showed increasing trends with the increase in flooding level in the last few years. The reasons behind this aregovernment supports, subsidies, incentives, and stress coping strategies towards accelerating national production to overcome the effects of the flood to sustain national food security; development of stress-tolerant and high yielding modern rice varieties by the research organizations; and replacing the local varieties with these modern varieties by the farmers and extension workers in Bangladesh.
Keywords: 630; Threshold regression; Flood; Rice area; Production; Food security